PENGARUH LINGKUNGAN KERJA FISIK, KOMPENSASI, DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA KANTOR PERUMDA PASAR MANGU GIRI SEDANA DI BADUNG - Luh Putu Meilya Widyasti; Ni Made Dwi Puspitawati; Gde Bayu Surya Parwita (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
Human resources in a company play an important role. Companies must be able to build and increase work productivity in their environment. In increasing the productivity of its employees, the company employs several methods, including the application of reasonable compensation, motivating applications, and the creation of conducive working conditions. This research aims to determine and analyze the influence of the physical work environment, compensation, and motivation on employee work productivity at the Perumda Pasar Mangu Giri Sedana Office in Badung. The population in this study was all 35 employees of the Perumda Pasar Mangu Giri Sedana Office in Badung. In this study, the sample size was determined using a saturated sample, namely all 35 employees of the Perumda Pasar Mangu Giri Sedana Office in Badung, with the data collection method using a questionnaire. The data analysis technique used in this research is multiple linear regression analysis. The results of the analysis show that (1) the physical work environment has a positive and significant effect on employee work productivity at the Pasar Mangu Giri Public Housing Office Sedana in Badung; (2) compensation has a positive and significant effect on employee work productivity at the Perumda Pasar Mangu Giri Sedana Office in Badung; and (3) work motivation has a positive and significant effect on employee work productivity at the Perumda Pasar Mangu Giri Sedana Office in Badung.